Building Powerful and Robust Websites with Drupal 6 - Mercer, David (Packt Publishing, 2011)
This book updates the bestselling Drupal: Creating Blogs, Forums, Portals, and Community Websites released for Drupal 4.7. David Mercer revisits the hugely popular Drupal CMS and expands, concentrates, and upgrades the original book to bring it line with the vastly improved latest version, Drupal 6. This book is for people with little or no experience in website design, people who are not familiar with PHP, MySQL or HTML, and above all people with little to no experience in using Drupal. Even intermediate Drupal users will find this book of interest although it is specifically aimed at pushing beginners up the learning curve.